Antibiotic Resistance of Staphylococcus aureus isolated from nasal cavity of Health Care Personnel. - Jasim, Hiba S. (Journal of the Faculty of Medicine Baghdad, 2013)
Background: Staphylococcus aureus infections are growing problems worldwide with important implications in hospitals. The organism is normally present in the nasal vestibule of about 35% apparently healthy individuals and its carriage varies between different ethnic and age groups.Objective:To study the antibiotic resistance of staphylococcus aureus isolated from nasal cavity of Health Care Personnel.Patients and methods: A total of 180 samples were collected from the nose of the  two groups (health care personnel, community control) at Baghdad Teaching Hospital. They were screened for nasal colonization with S.aureus during the period between April 2012 to September 2012, by using a sterile cotton swabs.Results: Nasal swabs with Staphylococcus aureus which isolated from health care personnel was 40%, while in community control was 33.33%.Conclusion: High prevalence rate of S. aureus nasal carriers was found among health care personnel of Baghdad Teaching Hospital. The highest rate was found in sub staff group. And among community control, high prevalence rate of S.aureus nasal carriers was found in the school students. All isolates of S. aureus were resistant to pencillin G, ampicillin, and erythromycin. Vancomycin was the most effective drugs against S.aureus, isolates and followed by rifampicin and fusidic acid.